Recruitment of highly cytotoxic CD8+ T cell receptors in mild SARS-CoV-2 infection - Wagner, Karolin I.; Mateyka, Laura M.; Jarosch, Sebastian; Grass, Vincent; Weber, Simone; Schober, Kilian; Hammel, Monika; Burrell, Teresa; Kalali, Behnam; Poppert, Holger; Beyer, Henriette; Schambeck, Sophia; et al. (Cell reports, 2022)
T cell immunity is crucial for control of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and has been studied widely on a quantitative level. However, the quality of responses, in particular of CD8+ T cells, has only been investigated marginally so far. Here, we isolate T cell receptor (TCR) repertoires specific for immunodominant SARS-CoV-2 epitopes restricted to common human Leukocyte antigen (HLA) class I molecules in convalescent individuals. SARS-CoV-2-specific CD8+ T cells are detected up to 12 months after infection. TCR repertoires are diverse, with heterogeneous functional avidity and cytotoxicity toward virus-infected cells, as demonstrated for TCR-engineered T cells. High TCR functionality correlates with gene signatures that, remarkably, could be retrieved for each epitope:HLA combination analyzed. Overall, our data demonstrate that polyclonal and highly functional CD8+ TCRs—classic features of protective immunity—are recruited upon mild SARS-CoV-2 infection, providing tools to assess the quality of and potentially restore functional CD8+ T cell immunity.
plus in CD8+ hochgestellt
Gesehen am 27.06.2023